Analisis Rasio Leverage dan Keputusan Investasi terhadap Nilai Perusahaan melalui Kebijakan Deviden Perusahaan - Maria Naus; Ratih Dewi Titisari Haryana (Akuisisi : Jurnal Akuntansi, 2025)
The purpose of this study is to examine several elements that affect the firm value of businesses listed on the LQ45 index of the Indonesia Stock Exchange. This study specifically examines how leverage ratio, investment choices, and dividend policy affect business value while taking into account the intervening effect of dividend policy. A purposive sampling procedure was used to select the company's annual financial statements for the period 2019–2023, which served as the data source. Twenty-five businesses that met the requirements to be sampled for the study were found through this approach. A path analysis approach was used in this study to test the causal relationship between the variables. The findings indicate that investment choices and leverage ratio have a significant impact on business value. Both factors are important markers of how businesses handle their financial structure and implement long-term growth strategies. In addition, it has been found that dividend policy serves as an intervening variable that strengthens the relationship between firm value, investment choices, and leverage ratio